The Class of Homothetic Isoquant Production Functions: Programming Revisited. - Clemhout, S. (Review of Economic Studies)
This article focuses on the class of homothetic isoquant production functions (HIPF). Programming for computers is exposed to subtle nuances because it remains something of an art. In this manner bugs take treacherous disguises; such a crept into the class of HIPF. This article hereby proceed to bug extermination. The end empirical results obtained in that paper are not substantially changed; however, the test for convexity is altered.